2021
DOI: 10.3389/fneur.2021.714313
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Application of a Quantitative Collateral Assessment Method in Acute Ischemic Stroke Patients With Endovascular Treatments: A Single-Center Study

Abstract: Objectives: To develop an efficient and quantitative assessment of collateral circulation on time maximum intensity projection CT angiography (tMIP CTA) in patients with acute ischemic stroke (AIS).Methods: Eighty-one AIS patients who underwent one-stop CTA-CT perfusion (CTP) from February 2016 to October 2020 were retrospectively reviewed. Single-phase CTA (sCTA) and tMIP CTA were developed from CTP data. Ischemic core (IC) volume, ischemic penumbra volume, and mismatch ratio were calculated. The Tan scale wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…There has been a connection between large infarct length and poor collateral circulation, according to previous studies, perhaps because the presence of a larger penumbra is associated with excellent movement within the collateral pathway, and the time window for possible reperfusion can be extended by prolonging the survival time of the penumbra [25]. According to a study published in 2021, ischemic stroke victims who present within 24 hours of onset have extremely high chances of surviving; the penumbra device permits for secure and effective revascularisation; in other phrases, properly collateral stream limits the enlargement of the infarct core and determines the final infarct volume [16]. Thus, CES related to atrial traumatic inflammation is related to more extreme hypoperfusion, main to larger infarct volumes, extra intense haemorrhagic transformation, and worse stroke outcomes than LAA [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a connection between large infarct length and poor collateral circulation, according to previous studies, perhaps because the presence of a larger penumbra is associated with excellent movement within the collateral pathway, and the time window for possible reperfusion can be extended by prolonging the survival time of the penumbra [25]. According to a study published in 2021, ischemic stroke victims who present within 24 hours of onset have extremely high chances of surviving; the penumbra device permits for secure and effective revascularisation; in other phrases, properly collateral stream limits the enlargement of the infarct core and determines the final infarct volume [16]. Thus, CES related to atrial traumatic inflammation is related to more extreme hypoperfusion, main to larger infarct volumes, extra intense haemorrhagic transformation, and worse stroke outcomes than LAA [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The electricity of the collateral circulation is extra essential for tissue fate than the collateral filling price [14,15]. The collateral stream is quite variable between individuals, and the optimum time of series is also in my view variable [16]. The CTP generates a couple of maps of ischemic tissue and is a regarded decision-making device for patients with acute ischemic stroke [17].…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of CS can be time-consuming, subjective, and the challenge for the manual scoring system is the low agreement between evaluators, making patient characterization less consistent. Several studies have shown that fully automated or semi-automated methods are a quantitative, reliable, time-saving, and user-independent measure of CS on baseline CTA ( 12 , 14 , 22 ). Semiautomated CS evaluation has been associated with clinical outcome previously in AIS patients treated with EVT ( 22 ), however, to the best of our knowledge the relationship between admission BP and automatically measured CS had not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…These interesting results revealed that the disagreement mainly occurred within the sets of Tan score 0 and 1 (0–50%) or Tan score 2 and 3 (50–100%). Recently, another quantitative measurement of the collateral circulation (V CCq ) was proposed—the method calculating vessel volumes using the identified CT values at three selected layers on time maximum intensity projection (tMIP) CTA images ( Cao et al, 2021 ). The study showed that both V CCq and Tan score were moderately negatively correlated with final infarct volume; however, unlike Tan score, V CCq was an independent predictive factor of the clinical outcome (OR = 0.14, P = 0.009).…”
Section: Discussionmentioning
confidence: 99%